Is real-time PCR-based diagnosis similar in performance to routine parasitological examination for the identification of Giardia intestinalis, Cryptosporidium parvum/Cryptosporidium hominis and Entamoeba histolytica from stool samples? Evaluation of a new commercial multiplex PCR assay and literature review. (February 2016) - Laude, A.; Valot, S.; Desoubeaux, G.; Argy, N.; Nourrisson, C.; Pomares, C.; Machouart, M.; Le Govic, Y.; Dalle, F.; Botterel, F.; Bourgeois, N.; Cateau, E.; et al.
Abstract: Microscopy is the reference standard for routine laboratory diagnosis in faecal parasitology but there is growing interest in alternative methods to overcome the limitations of microscopic examination, which is time-consuming and highly dependent on an operator's skills and expertise. Compared with microscopy, DNA detection by PCR is simple and can offer a better turnaround time. However, PCR performances remain difficult to assess as most studies have been conducted on a limited number of positive clinical samples and used in-house PCR methods. Our aim was to evaluate a new multiplex PCR assay (G-DiaParaTrio; Diagenode Diagnostics), targeting Giardia intestinalis, Cryptosporidium parvum/Cryptosporidium hominis and Entamoeba histolytica . To minimize the turnaround time, PCR was coupled with automated DNA extraction (QiaSymphony; Qiagen). The PCR assay was evaluated using a reference panel of 185 samples established by routine microscopic examination using a standardized protocol including Ziehl–Neelsen staining and adhesin detection by ELISA ( E. histolytica II; TechLab). This panel, collected from 12 French parasitology laboratories, included 135 positive samples for G. intestinalis ( n = 38), C. parvum/C. hominis ( n = 26), E. histolytica ( n = 5), 21 other gastrointestinal parasites, together with 50 negative samples. In all, the G-DiaParaTrio multiplex PCR assay identified 38 G. intestinalis, 25 C. parvum/C. hominis and five E. histolytica leading to sensitivity/specificity of 92%/100%, 96%/100% and 100%/100% for G. intestinalis, C. parvum/C. hominis and E. histolytica, respectively. This new multiplex PCR assay offers fast and reliable results, similar to microscopy-driven diagnosis for the detection of these gastrointestinal protozoa, allowing its implementation in routine clinical practice.